Perlindungan Data Pribadi sebagai Hak Asasi di Era Digital: Menggagas Paradigma Konstitusional dalam Arsitektur Privasi Indonesia - Gilang Rizki Aji Putra (BULETIN ADALAH, 2022)
Digital transformation has turned personal data from identity information into a tradable asset. This article examines personal data protection within a human rights framework and evaluates Indonesia’s regime under Law No. 27/2022 on Personal Data Protection (PDP Law). Using conceptual, statutory, and comparative approaches, the study finds that the PDP Law provides a legal foundation but still faces challenges involving independent supervision and remedies for data subjects. Personal data protection represents privacy, dignity, and constitutional rights. The article recommends establishing an independent supervisory authority and strengthening digital literacy. Keywords: Personal Data Protection, Human Rights, Digital Privacy, PDP Law, Constitutional Rights.